Counseling and Installation of Contraception Implant Devices in Women of Childbearing Age - Carolin, Bunga; Novelia, Shinta; Ermiyati (Rajaki of Tulip Medika Publisher, 2024)
One effort to reduce the rate of population growth is through a family planning program for couples of childbearing age. Implants are a long-term contraceptive method that is highly effective in preventing pregnancy. However, in its implementation, the use of implants is still far from the target. The public's low interest in using implants is partly due to the fear and anxiety of potential acceptors about installing the contraceptive device. One effort to increase interest in using implants can be done through outreach. In this counseling, the method used is providing educational material about implants and continuing with implant installation. This program will be implemented in Sawangan District, Depok City, West Java. It is hoped that this activity can increase knowledge and awareness of women of childbearing age about the importance of long-term contraception such as implants.